Diversity of Soil Macrofauna in Lembah Harau, West Sumatra - Dwi Savitri Nur Hidayah; Mahya Ihsan; Dara Septia Syafitri (DIVERSITAS HAYATI, 2023)
Soil macrofauna constitutes fauna that inhabits both the soil surface and subsurface. Soil macrofauna plays a crucial role in ecosystems by safeguarding soil fertility through the decomposition of organic matter within the soil. Biodiversity is an essential aspect supporting the sustainability of living organisms on Earth. Macrofauna can serve as bioindicators of environmental quality, particularly soil conditions. The presence of soil macrofauna aids in the land recovery process by enhancing the physical, chemical, and biological properties of the soil. The objective of this research is to identify the diversity of soil macrofauna in varying environmental conditions. The employed methodology involves surveys and direct observations conducted in the Lembah Harau Forest Area in the Payakumbuh City of Limapuluh Kota Regency, West Sumatra Province. Sampling is conducted using monoliths in aquatic environments, canopy-covered areas, and open regions. The central portion of the monolith is excavated at depths of 10 cm, 20 cm, and 30 cm successively, followed by hand sorting. The diversity of soil macrofauna discovered falls into the moderate category (H'=2.77) with a macrofauna evenness of 0.726. These values are within the moderate range, indicating a relatively even distribution of soil macrofauna in the surveyed location. The predominant species identified is Ruticulitermes Hesperus.